2017
DOI: 10.1111/pce.12987
|View full text |Cite
|
Sign up to set email alerts
|

The boron transporter BnaC4.BOR1;1c is critical for inflorescence development and fertility under boron limitation in Brassica napus

Abstract: Boron (B) is an essential micronutrient for plants, but the molecular mechanisms underlying the uptake and distribution of B in allotetraploid rapeseed (Brassica napus) are unclear. Here, we identified a B transporter of rapeseed, BnaC4.BOR1;1c, which is expressed in shoot nodes and involved in distributing B to the reproductive organs. Transgenic Arabidopsis plants containing a BnaC4.BOR1;1c promoter-driven GUS reporter gene showed strong GUS activity in roots, nodal regions of the shoots and immature floral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…Brassica napus cv. Qingyou10 ( Q10 ) and Westar10 ( W10 ) are B‐efficient and B‐inefficient cultivars, respectively, and served to study physiological, molecular and genetic factors influencing B efficiency (Zhao et al ., ; Yang et al ., ; Zhang et al ., ,b, ; Yuan et al ., ; Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brassica napus cv. Qingyou10 ( Q10 ) and Westar10 ( W10 ) are B‐efficient and B‐inefficient cultivars, respectively, and served to study physiological, molecular and genetic factors influencing B efficiency (Zhao et al ., ; Yang et al ., ; Zhang et al ., ,b, ; Yuan et al ., ; Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested that transcript and protein abundance of BnaC04.BOR1;1c adds to the B deficiency tolerance of cv. Q10 due to the fact that a knockdown mutant suffered from severe shoot and flower B deficiency symptoms when grown in B-deficient growth conditions (Zhang et al, 2017;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research milestones included the identification of a boric acid channel, NIP5;1, and a boric acid/borate exporter, BOR1, from Arabidopsis thaliana (Takano et al 2008). There is increasing evidence that the boron transporters are generally important for plant development, for instance in roots and shoot nodes and for the development of inflorescence tissues (Zhang et al 2017).…”
Section: Role Of Boron Compounds In Plantsmentioning
confidence: 99%
“…In Arabidopsis, NIP5;1 and BOR1 are polarly localized at the distal and proximal side of the plasma membrane of the root cells, respectively (Takano et al, 2010), and their cooperative transport is required for efficient and directional uptake of B in the roots especially under a B-limited condition Reid 2014). Homologs of Arabidopsis NIP5;1 and BOR1 have been functionally characterized in other plant species such as rice (Oryza sativa), barley (Hordeum vulgare), rapeseed (Brassica napus), and maize (Zea mays; Nakagawa et al, 2007;Sutton et al, 2007;Chatterjee et al, 2014;Durbak et al, 2014;Hanaoka et al, 2014;Leonard et al, 2014;Zhang et al, 2017). Basically, they have a similar role in B uptake, although the expression patterns differ somewhat within plant species.…”
mentioning
confidence: 99%